Mesenchymal Stem Cells Provide Neuroprotection by Regulating Heat Stroke-Induced Brain Inflammation - Zhang, Yu; Deng, Zihui; Li, Yun; Yuan, Rui; Yang, Mengmeng; Zhao, Yan; Wang, Lu; Zhou, Feihu; Kang, Hongjun (Frontiers in Neurology, 2020)
Heat stroke (HS) is the most acute type of heat illness accompanied with serious central nervous system (CNS) dysfunction. Despite the pathological process being clearly studied, effective treatment is deficient. Currently, mesenchymal stem cells (MSCs) have been demonstrated to have neuroprotective effects as there are no old ones. Thus, the purpose of the present study was to explore the neuroprotective effects and mechanisms of MSCs against HS-induced CNS injury. HS in rat models was induced by a high-temperature environment and treated with MSCs via the tail vein. The results demonstrated that MSC injection significantly reduced the mortality and inhibited the circulation inflammatory response. Moreover, the HS-induced neurological deficit and neuronic damage of the hippocampus were significantly ameliorated by MSC administration. In addition, MSC administration significantly restored astrocytes and inhibited cerebral inflammatory response. These results indicate that MSC infusion has therapeutic effects in HS of rats by regulating the circulation and cerebral inflammatory response. Moreover, astrocytes increased in MSC-treated HS rats when compared with the untreated ones. This may suggest a potential mechanism for HS prevention and therapy through MSC administration.